PENGARUH MARKETING CAPABILITIES TERHADAP FINANCIAL PERFORMANCE PADA INDUSTRI PERHOTELAN DI SURABAYA DENGAN CORPORATE REPUTATION SEBAGAI VARIABEL INTERVENING - Sanjaya, Fenny (Business Accounting Review, 2016)
This study aimed to know the direct andÂ significant affect of marketing capabilities to corporate reputation, corporate reputation to financial performance and marketing capabilities toÂ financial performance in the hospitality industry in Surabaya. Also to examine the significant indirect affect on the financial capabilities to marketing performance through corporate reputation in the hospitality industry in Surabaya. This study used a quantitative approach, and the data were obtained by distributing questionnaires to hospitality industries in Surabaya then processed by using smartPLS software. This study showed that there was a positive and significant relationship of marketing capabilities to corporate reputation; corporate reputation to financial performance; and marketing capabilities to financial performance in hospitality industries in Surabaya.Â Corporate reputation was not adequate to become variable intervening between marketing capabilities and financial performance. The direct relationship between financial performance and marketing capabilities gave bigger influence than through corporate reputation